Psychophysiological state and decision making in wrestlers - Korobeynikov, G.; Korobeinikova, L.; Raab, M.; Korobeinikova, I.; Danko, T.; Kokhanevich, A.; Cynarski, W. J.; Mytskan, T. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. The investigation of psychophysiological functions in athletes is important to adapt the training process. In this paper, we examine speed perception and decision-making during wrestling fights as a crucial component of performance. We argue that a wrestler must anticipate the situation and speeded choices of response selection are required based on fast and frugal decision-making. Aim. The approach investigates a psychophysiological test battery to test correlates of fast or slow decision making in wrestlers. Method. 29 elite Greco-Roman wrestlers were examined. The psychophysiological states of wrestlers were studied by a test battery of vision motor test, non-verbal intelligence, anticipation and heart rate variability. Those competences are correlated to fast or slow decision-making time when choosing between different stimuli. Results. The analysis revealed correlation between fast decision-making and visual perception, the increase of impulsiveness and level of emotional strain during fights. In addition, faster decision- making was present in those wrestlers with high anticipation ability and balance between processes of arousal and inhibition. The psychophysiological data suggests that fast decision-making correlates with the autonomic regulation of the heart rate. Conclusions. Fast decision-making in wrestlers seems to be related to a number of parameters in a psychophysiological test battery calling for a causal and experimental approach in the future and specific training of those factors allow wrestlers to improve their decision time.